Establishment of an Individual Limited Liability Company: Opportunities and Regulatory Challenges in Indonesia - Nurhidayati Nurhidayati; Dini Inasyah Alfaridah; Dina Aisyah Alfarijah (Universitas Bina Sarana Informatika, 2026)
Indonesia’s Job Creation Law No. 6 of 2023 introduces a significant regulatory innovation by permitting Individual Limited Liability Companies (PT Perorangan) to facilitate Micro and Small Enterprises (MSEs) formalization. Despite this progressive legal reform, scholarly research addressing the practical opportunities and implementation challenges remains limited, particularly from management and business operation perspectives. This study examines the legal characteristics, entrepreneurial opportunities, and organizational challenges of establishing Individual LLCs, with emphasis on implications for MSE strategic decision-making, business operations, and sustainable growth. This research employs a normative juridical methodology with statutory and conceptual approaches, analyzing primary legal materials (Law No. 6/2023, Government Regulations No. 7-8/2021, Ministerial Regulation No. 21/2021) and secondary legal literature. Qualitative descriptive analysis identifies opportunities including procedural simplification, reduced establishment costs (IDR 50,000), and enhanced legal entity legitimacy, and examines challenges including inadequate legal literacy among target entrepreneurs, weak corporate governance mechanisms in single-founder structures, limited bank credit assessment frameworks for Individual LLCs, unclear business succession procedures, and technical barriers in digital registration systems. The study reveals that while Individual LLCs present genuine opportunities for MSE formalization, their effectiveness depends critically on complementary institutional support, enhanced legal literacy programs, and clarified governance frameworks. This research contributes to corporate law scholarship and management practice by providing comprehensive analysis of Individual LLC implementation challenges from both legal and organizational perspectives, and recommends specific regulatory improvements and institutional initiatives necessary to maximize the policy’s contribution to MSE empowerment and national economic development.